Ferritinophagy, a form of autophagic ferroptosis: New insights into cancer treatment - Sun, Kai; Li, Chenyuan; Liao, Shichong; Yao, Xinrui; Ouyang, Yang; Liu, Yi; Wang, Zhong; Li, Zhiyu; Yao, Feng (Frontiers in Pharmacology, 2022)
Ferritinophagy, a form of autophagy, is also an important part of ferroptosis, a kind of regulated cell death resulting from abnormal iron metabolism involving the production of reactive oxygen species. As the relations of ferroptosis, autophagy and cancer were revealed, ferritinophagy has attracted increasing attentions in cancer development. In this review, we discuss the latest progress on ferroptosis, autophagy-associated ferroptosis led by ferritinophagy, the regulators of ferritinophagy and promising cancer treatments that targets ferritinophagy. Ferritinophagy is at the intersection of ferroptosis and autophagy, playing a significant role in cancer development. These studies provide new insights into the mechanisms of ferritinophagy and its promising treatments for cancer.